Effect of condensed tannins in sainfoin on in vitro protein solubility of lucerne as affected by the proportion of sainfoin in the mixture and the preserving conditions - Aufrère J.; Dudilieu M.; Poncet C.; Baumont R.; Dumont B. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The present work was designed to assess the effects of condensed tannins (CT) of sainfoin (S) on the solubility of Lucerne (L) proteins when the 2 forages are mixed in different proportions in fresh or conserved forms (freeze dried or oven dried at 40°C or 60°C). The percentages of L:S were 100:0, 75:25, 50:50, 25:75, 0:100) for all preparations. Fresh forages were chopped and either mixed and homogenised in a Waring blender and incubated fresh, or dried and ground prior to incubation. Nitrogen solubility tests (SolN) in artificial saliva buffer (expressed as % of total N) and protein N (in SolN) after precipitation with TCA (expressed as % Nt) were performed on all preparations in the presence or absence of PEG (polyethylene glycol 4000) to assess the tannin effect. Nitrogen solubility was low for fresh and freeze dried sainfoin (10% of total N) and approximately doubled after oven drying (p<0.05). The main component of sainfoin SolN was non-protein N. In contrast, soluble nitrogen in fresh lucerne was high (57% Nt) and decreased slightly in dried samples. The SolN was mainly protein N (65% SolN) in fresh and freeze-dried samples and 40% SolN in oven-dried samples. The N solubility and percentage of protein in SolN decreased as the percentage of sainfoin increased. After PEG addition, which binds with tannins, SolN was not affected for lucerne but increased considerably for sainfoin (p<0.05). SolN in mixtures (without PEG) was lower than that calculated from N solubility of each forage of the mixture so that CT from sainfoin insolubilized some lucerne proteins. This effect was greater with fresh than with dried forages. The data support the hypothesis that the degree of binding between CT with plant protein is affected by the preservation method. Condensed tannins in sainfoin can reduce in vitro N solubility of other forages (e.g. lucerne) when intimately mixed. This effect is greater with fresh than with dried forages such as hays.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)